A novel approach for robust model predictive control applied to switched linear systems through state and output feedback - Carvalho, Luis; Costa, Marcus V. S.; Macedo, Leonardo H. [UNESP]; Fortes, Elenilson V. (Elsevier, 2023)
This paper proposes a robust switched model-based predictive controller design for discrete linear systems with state constraints, inputs, and disturbances limited in norm. Modeled via linear matrix inequalities, the online and offline designs of the proposed control aim at minimizing the upper bound of the quadratic performance index for a horizon of infinite prediction associated with the state estimator and the switching rule, seeking to guarantee the robust stability for closed-loop systems. To this end, three theorems are formulated. To demonstrate the effectiveness of the control strategy, a comparative analysis is performed between the performance of the proposed model and a benchmark method. From the results, it is possible to conclude that the proposed method is promising in the scope of control of linear systems subject to switching, being more efficient than the benchmark for the stabilization and control of both numerical examples.
Keywords: Linear matrix inequalities; Model predictive control; Output feedback; Stable invariant ellipsoids; State feedback; Switched systems